Penguatan Desain Dakwah Masjid di Era Milenilal melalui Android - Jasuri, Jasuri; Khalif, M. Ardhi; Anwar, Edi Daenuri (LP2M of Institute for Research and Community Services - UIN Walisongo, 2019)
Dedication work with the title